Batasan Kewajiban Nafkah dalam Upaya Preventif Cerai Gugat: Studi Pada Pengadilan Agama Kota Pekanbaru - Niko, Ferlan; Akbarizan, Akbarizan; Nurcahaya, Nurcahaya (Tazkir: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2025)
The increasing number of divorce cases in Indonesia, particularly due to the failure to fulfill alimony obligations, indicates structural problems in the practice of Islamic family law and its implementation in the Religious Court. The lack of clarity regarding the normative and operational boundaries of fair and proportional alimony often triggers domestic conflicts that lead to divorce. This study aims to analyze the limits of alimony obligations in divorce cases in the Religious Court of Pekanbaru City and assess its role as a preventive instrument for divorce. The study uses a qualitative approach with a juridical-empirical method combined with normative-doctrinal analysis. Data was obtained through a study of divorce decisions from 2019 to 2023 and in-depth interviews with judges and court officials. The analysis was conducted descriptively and analytically using the perspectives of family law protection, gender justice, and maqasid al-syari'ah. The results of the study show that the significant increase in divorce lawsuits is influenced by the non-fulfillment of financial support, both absolutely and relatively, which is exacerbated by the absence of clear standards for adequate financial support in judicial practice. Financial support is understood not only as a minimum financial obligation but also as an instrument of relational justice that affects family stability. This study concludes that affirming the contextual and operational limits of alimony obligations has the potential to become a preventive instrument for divorce. The implications of this study emphasize the need to strengthen alimony assessment standards, family law education, and more responsive and equitable judicial policies.